UPAYA HUKUM ATAS PUTUSAN P.N. KUDUS DALAM PEMBATALAN PUTUSAN ARBITRASE - ANGGO DOYOHARJO (Universitas Slamet Riyadi, 2009)
Abstract:Arbitrage clausal in agreement between PT Pura Barutama and Perum Peruri has been conducted by Badan Arbitrase Nasional Indonesia (Indonesian National Arbitrage Board) with the winner in Perum Peruri. However, PT Pura Barutama asked for objection to Pengadilan Negeri Kudus (Kudus State Court) and the winner is PT Pura Barutama. Perum Peruri, however, does not agree with this decision and asked for objectin to the General Attorney and once again, the winner is Perum Peruri. Keywords: Arbitrage decision cancellation.